Trust in the Digital Era: Analysis of the Influence of Reputation and e-WOM on Fashion Purchasing Decisions on Shopee - Suwardani, Eka; Mahendri, Wisnu (Universitas Kadiri, 2025)
This study aims to analyze the influence of reputation and electronic word of mouth on purchasing decisions for fashion products on Shopee, by considering the role of consumer trust as an intervening variable. Respondents involved in this study were 105 Shopee consumers who had purchased fashion products. The method used in this study is Structural Equation Modeling (SEM) with the help of Smart PLS software to test the influence between variables. The results of the study indicate that reputation does not affect consumer trust, and reputation does not affect purchasing decisions either directly or through consumer trust as an intervening variable. However, electronic word of mouth is proven to have a significant influence on purchasing decisions and electronic word of mouth has a significant influence on purchasing decisions through consumer trust. These findings provide insight into the importance of eWOM in influencing purchasing decisions on e-commerce platforms, and show that reputation does not play a major role in influencing trust and purchasing decisions on the Shopee platform in fashion products.